A construção da agenda governamental e midiática de políticas de combate à corrupção no governo Dilma Rousseff (2011-2016) : identificando eventos críticos de convergência e divergência entre as agendas - Faleiros, Laís Bertholino (2017)
For the first time, in the year of 2015, public opinion chose, in a DataFolha survey, corruption as the main Brazilian problem. Given this fact, the present work set out to investigate the media and governmental agenda of anti-corruption policies in the Federal Government during the two mandates of Dilma Rousseff (2011-2016), to recognize critical events in both agendas and to analyze their convergent and divergent points. In order to do so, it was used Baumgartner and Jones' (2006) Punctuated Equilibrium model to demonstrate the variations of the corruption issue within the agendas addressed. This dissertation found critical events such as Operation Lava Jato, which gives meaning to the process of building agendas in this period and explains the variation of agendas in the year of 2014, but it is not possible only in a six-year period identify a significant rupture in the governmental agenda anti-corruption policies, but only a few incremental innovations. Whereas in the media agenda the ruptures of the balance are clearer, since a corruption scandal is enough to generate impact in the volume of the news content and to increase the incidence of the subject in the agenda of the media.